Antimicrobial peptide LL-37 circulating levels in chronic obstructive pulmonary disease patients with high risk of frequent exacerbations - Yang, Yi-Meng; Guo, Yan-Fei; Zhang, Hong-Sheng; Sun, Tie-Ying (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Background: Exacerbations of chronic obstructive pulmonary disease (COPD) increase the decline in lung function, deterioration in health status and risk of death. The assessment of exacerbation risk is important in the grading of COPD. The most common cause of COPD exacerbation is respiratory tract infection. The only known human cathelicidin antimicrobial peptide, LL-37, play an important role in innate defense against infection. Its gene expression is regulated by the bioactive form of vitamin D. The objective of the present study was to explore the relationship between LL-37 plasma levels, vitamin D status and exacerbation risk in patients with COPD. Methods: COPD patients and normal subjects were recruited from Beijing Hospital for this study. COPD patients were divided into low risk group and high risk group according to the criteria of GOLD strategy. The plasma concentrations of LL-37 were measured by ELISA technique to explore the difference in LL-37 levels between groups. The plasma levels of 25-hydroxy vitamin D [25(OH)D] were analyzed using electrochemiluminescence immunoassay (ECLIA). Results: A total of 84 COPD patients and 51 normal subjects (control group) were recruited. COPD patients were divided into low risk group (37 cases) and high risk group (47 cases), depending on forced expiratory volume in one second (FEV1)%pred and exacerbation frequency in the previous year. The plasma concentrations of LL-37 in control group, low risk group and high risk group were 20.7±5.8, 19.5±4.1 and 17.9±3.9 μg/L respectively. The plasma concentration of LL-37 was significantly lower in high risk group than in control group (P=0.006). But there was no significant difference between low risk group and high risk group (P=0.152). The plasma concentrations of 25(OH)D in control group, low risk group and high risk group were 18.1±9.4, 13.1±6.9 and 9.3±5.8 ng/mL respectively. The plasma concentration of 25(OH)D was significantly higher in control group than in low risk group (P=0.004) or high risk group (P